Development of an Evaluation Model of Pracharath School in Southern Border Provinces: An Application of Multiple Evaluation Approaches - Komontree, Natchaya; Rorbkorb, Narongsak; Tansakul, Jirawat; Rascha, Teerayout (Journal of Human and Society, Sisaket Rajabhat University, 2024)
The Pracharat School Project in the Southern Border Provinces is a significant government initiative aimed at creating educational opportunities for students in these area. To ensure the project's implementation aligns with real conditions and provides beneficial recommendations for its effective development, utilizing various evaluation concepts is deemed appropriate for this research. This study examines the synthesis of the components and indicators for project evaluation, and the development and verification of the quality of the evaluation model. Data were gathered from five experts in measurement, evaluation, and the context of Pracharat schools in the southern border provinces. The instruments for the study included: 1) a synthesized evaluation model form and 2) an evaluation model suitability assessment form. The research procedure comprised three steps: 1) synthesizing relevant documents, 2) developing the evaluation model, and 3) evaluating the evaluation model. A multi-method evaluation was completed using descriptive statistics and qualitative procedures. Results reveal that 1) The synthesis of components and indicators for evaluation, through the application of multi-concept evaluation, consists of five components: system evaluation, input factors, process, output, and follow-up. 2) The development and quality verification of the project evaluation model yielded five components and fifteen indicators, as follows: three indicators for system evaluation, three indicators for input factors, three indicators for process, three indicators for output, and three indicators for follow-up. And 3) The evaluation of the project model showed an average score of 4.92, indicating the highest level of suitability for use in creating project evaluation tools.